Caregiver experiences and perceptions of stroke - Mary Thomas; Kirston Greenop (AOSIS, 2008)
With the increasing prevalence of people in developing countries who suffer strokes, the long-term care of people who have had a stroke and who are living with disabilities has substantial consequences for caregivers and their respective families. As the caregiver plays a pivotal role in the rehabilitation of the people who have had a stroke, the objectives of this study constitute an investigation into the complexities of caregiving, including both perceptions and experiences of the healthcare system. Semi-structured interviews were utilised to elicit post-stroke experiences of six caregivers. The challenge the South African context adds to these experiences was probed. The data were analysed qualitatively by thematic and content analysis. Prominent themes associated with caregiving included: role changes and relationship disruptions within the family, occupational and social implications, fatigue, anxiety, depression, loneliness, frustration as well as financial problems. Caregiver experiences were exacerbated by the inadequate support structures available. The results are interpreted within a biopsychosocial approach, concluding with the concerns raised by caregivers on the support they require from the healthcare system in order to provide home-based care. Opsomming Met die toenemende voorkoms van beroerte in ontwikkelende lande bring die langdurige versorging van pasiënte met gestremdheid beduidende gevolge vir sorggewers en hulle onderskeie gesinne mee. Aangesien die sorggewer 'n sleutelrol in die rehabilitasie van die beroertepasiënt speel, behels die doelstellings van hierdie studie 'n ondersoek na die verwikkeldhede van versorging, wat sowel persepsies as ondervinding van die gesondheidsorgstelsel insluit. Semi- gestruktureerde onderhoude is aangewend om die na-beroerte ondervindings van ses sorggewers te peil. Die uitdaging wat die Suid- Afrikaanse konteks tot hierdie ondervindings meebring is ondersoek. Die data is kwalitatief deur middel van tematiese en inhoudsanalise ontleed. Prominente temas wat verbandhou met sorggewing sluit in: rolverandering en verhoudingsteurnisse binne die huisgesin, beroeps- en sosiale implikasies, uitputting, angs, depressie, eensaamheid, frustrasie sowel as finansiële probleme. Die probleme van sorggewers word vererger deur ontoereikende steunstrukture. Die resultate word binne 'n biopsigososiale benadering ontleed, en saamgevat met probleme wat sorggewers uitspreek ten opsigte van die steun wat hulle van die gesondheidsorgstelsel benodig om tuisgebaseerde sorg te kan voorsien.